A Biphasic Feature of Gli1+-Mesenchymal Progenitors during Cementogenesis That Is Positively Controlled by Wnt/β-Catenin Signaling. (October 2021) - Xie, X.; Xu, C.; Zhao, H.; Wang, J.; Feng, J.Q.
Cementum, a specialized bony layer covering an entire molar root surface, anchors teeth into alveolar bone. Gli1, a key transcriptional activator in Hedgehog signaling, has been identified as a mesenchymal progenitor cell marker in various tissues, including the periodontal ligament (PDL). To address the mechanisms by which Gli1 + progenitor cells contribute to cementogenesis, we used the Gli1 lacZ/+ knock-in line to mark Gli1 + progenitors and the Gli1 CreERT2/+ ; R26R tdTomato/+ line (named Gli1 Lin ) to trace Gli1 progeny cells during cementogenesis. Our data unexpectedly displayed a biphasic feature of Gli1 + PDL progenitor cells and cementum growth: a negative relationship between Gli1 + progenitor cell number and cementogenesis but a positive correlation between Gli1-derived acellular and cellular cementoblast cell number and cementum growth. DTA-ablation of Gli1 Lin cells led to a cementum hypoplasia, including a significant reduction of both acellular and cellular cementoblast cells. Gain-of-function studies (by constitutive stabilization of β-catenin in Gli1 Lin cells) revealed a cementum hyperplasia. A loss of function (by conditional deletion of β-catenin in Gli1 + cells) resulted in a reduction of postnatal cementum growth. Together, our studies support a vital role of Gli1 + progenitor cells in contribution to both types of cementum, in which canonical Wnt/β-catenin signaling positively regulates the differentiation of Gli1 + progenitors to cementoblasts during cementogenesis.